Universal : a guide to the cosmos - Cox, Brian, 1968-; Forshaw, J. R. (Jeffrey Robert), 1968- (Da Capo Press, 2017)
In this journey of scientific exploration, the authors consider some of the most fundamental questions about our Earth, Sun, and solar system--and the star-filled galaxies beyond. How big is our solar system? How quickly is space expanding? How big is the universe? What is it made of? Some of these questions can be answered on the basis of observations you can make in your own backyard. Other answers draw on the astonishing information now being gathered by teams of astronomers operating at the frontiers of the known universe.